Therapeutic Effectiveness of Approaches Applied in Teachers with Functional Vocal Disorders - Jerez, Rodrigo Maximiliano (Revista Chilena de Fonoaudiología, 2016)
This paper constitutes a bibliographic review on the effectiveness of therapeutic/training approaches applied in teachers with vocal alterations. Research has been designed in a retrospective and observational way, with a systemic review methodology based on publications from papers indexed in PubMed, SciELO, Scopus and Cochrane databases, as well as specialized journals such as American Speech-Language-Hearing Association (ASHA), Journal of Voice, CEFAC and Redalyc. The review of the material showed positive results for the different approaches. In varying proportions each one contributes to improve voice quality, hold the balance between the components that build the emission and prolong the harmony which should sustain the voice.